If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 8(b + 9a) = 0 Reorder the terms: 2a + 8(9a + b) = 0 2a + (9a * 8 + b * 8) = 0 2a + (72a + 8b) = 0 Combine like terms: 2a + 72a = 74a 74a + 8b = 0 Solving 74a + 8b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8b' to each side of the equation. 74a + 8b + -8b = 0 + -8b Combine like terms: 8b + -8b = 0 74a + 0 = 0 + -8b 74a = 0 + -8b Remove the zero: 74a = -8b Divide each side by '74'. a = -0.1081081081b Simplifying a = -0.1081081081b
| 9y-26=-18+y | | r*6=10 | | 3r-9=-7+r | | q*2=50 | | X-(y-Y)=6 | | 3(3n+1)=9(5n+1)+1 | | x+83+x+63+40=180 | | 5(n-7)=-35+5n | | 0=-4t^2+t+9 | | -7(2T+6)=-14 | | 0.4x-14=20 | | 6x+y=zforx | | 4(F-7)=24 | | 2xy-7y=5 | | -8(S+4)=-12 | | 13s-3=10 | | x+54+x+82+56=180 | | -4(n+7)+1=-4n-23 | | 150=4(6*5)+2(6h) | | bx+a=ab | | 7x+14=3x+34 | | 2x-7=-6X+17 | | 4(4S+2)=136 | | (6+y)-Y=6 | | .5x+1=-.67+15 | | 6x^2+24x=42 | | 3y-3-5y=3-2y | | 4n-5=6 | | -7m-4m=22 | | 150=4(6*4)+2(6h) | | l+8=26 | | f*-2=2*-2+5 |